Legumes under environmental stress : yield, improvement and adaptations - Azooz, M. M.; Ahmad, Parvaiz (Hoboken, NJ : John Wiley & Sons Inc., 2015)
The improvement of crop species has long been a goal since cultivation began thousands of years ago. To feed an ever increasing world population will require a great increase in food production. Wheat, corn, rice, potato and legumes are expected to lead as the most important crops in the world. Due to environmental fluctuations legumes are often exposed to different environmental stresses, leading to decreased yield and problems with growth and development of the legumes. The present work will cover the physiobiochemical, molecular and omic approaches and responses of legumes towards environm.
3.7 Storage proteins in legumes and effect of nutritional deficiency3.8 Protective mechanisms triggered in legumes under stress; 3.8.1 Drought and salinity stress; 3.8.2 Cold stress; 3.9 Conclusion; References; Chapter 4 Chickpea: Role and responses under abiotic and biotic stress; 4.1 Introduction; 4.2 Origin and occurrence; 4.3 General botany; 4.4 Nutritional uses; 4.5 Abiotic stress; 4.6 Chickpea and abiotic stress: The 'omics' approach; 4.6.1 Proteomics; 4.6.2 Transcriptomics; 4.6.3 Genomics; 4.6.4 Transgenomics; 4.7 Biotic stress; 4.7.1 Chickpea and diseases.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Legumes -- Effect of stress on; Legumes -- Yields; Legumes -- Adaptation; Biodegradation, Environmental; Bioremediation; Legumes; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; Electronic books